ANALISIS PENGARUH ARUS KAS OPERASI DAN LABA AKUNTANSI TERHADAP RETURN SAHAM PERUSAHAAN PERAIH INVESTMENT AWARD (BEST ISSUERS) DI BURSA EFEK INDONESIA - Ika Neni Kristanti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
Investors in investing always expect high stock returns. Therefore, investors should beable to assess which companies have good performance, so the stock return is also high. Thefinancial statements, particularly those relating to information on changes in operating cashflows and corporate accounting profit, are one of the important information that can be usedby investors to assess company performance. This study aims to provide empirical evidencerelated to the effect of operating cash flow and accounting earnings on stock returns.The data in this study is secondary data obtained from the company's annual financialstatements in Indonesia Capital Market Directory (ICMD) and Indonesia Stock Exchange(IDX). This study was conducted using the company population of the company winning theinvestment award (best issues) 2017 listed on the Indonesia Stock Exchange in 2015 and 2016.The result of this research is partially variable of operating cash flow (AKO) havepositive and significant effect to stock return, while partially, variable of accountancy profit(LAK) have no effect to stock return and simultaneously variable operating cash flow (AKO)and change of accountancy profit (LAK) jointly have a significant effect on stock returns inthe company's winning investment award (best issues) 2017 listed on the Indonesia StockExchange in 2015 and 2016.Keywords: Operating Cash Flow, Accounting Profit, and Stock Return